The peculiar challenge of bringing CAR-T cells into the brain: Perspectives in the clinical application to the treatment of pediatric central nervous system tumors - Del Baldo, Giada; Del Bufalo, Francesca; Pinacchio, Claudia; Carai, Andrea; Quintarelli, Concetta; De Angelis, Biagio; Merli, Pietro; Cacchione, Antonella; Locatelli, Franco; Mastronuzzi, Angela (Frontiers in Immunology, 2023)
Childhood malignant brain tumors remain a significant cause of death in the pediatric population, despite the use of aggressive multimodal treatments. New therapeutic approaches are urgently needed for these patients in order to improve prognosis, while reducing side effects and long-term sequelae of the treatment. Immunotherapy is an attractive option and, in particular, the use of gene-modified T cells expressing a chimeric antigen receptor (CAR-T cells) represents a promising approach. Major hurdles in the clinical application of this approach in neuro-oncology, however, exist. The peculiar location of brain tumors leads to both a difficulty of access to the tumor mass, shielded by the blood-brain barrier (BBB), and to an increased risk of potentially life-threatening neurotoxicity, due to the primary location of the disease in the CNS and the low intracranial volume reserve. There are no unequivocal data on the best way of CAR-T cell administration. Multiple trials exploring the use of CD19 CAR-T cells for hematologic malignancies proved that genetically engineered T cells can cross the BBB, suggesting that systemically administered CAR-T cell can be used in the neuro-oncology setting. Intrathecal and intra-tumoral delivery can be easily managed with local implantable devices, suitable also for a more precise neuro-monitoring. The identification of specific approaches of neuro-monitoring is of utmost importance in these patients. In the present review, we highlight the most relevant potential challenges associated with the application of CAR-T cell therapy in pediatric brain cancers, focusing on the evaluation of the best route of delivery, the peculiar risk of neurotoxicity and the related neuro-monitoring.